Ethical and security issues associated to the usage of technologies regarding with information and knowledge on the health field. - Alain Francisco Morejón Giraldoni; Esteban Hernández Barrio; Teresita del Carmen Rodríguez Izaguirre; Jirlén Moreno Torres; Aimee Seife Echevarría (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2008)
Cuban people are going to go to the construction of the informational society based on the principles of equity and accessibility. The health field or area is not distant to this development, so it is of special interest the ethical treatment of the usage of the new technologies of the informational area, so that the fulfillment of the confidentialness, integrity, and availability requisites through computer science safeness is allowed.